Rice bean (Vigna umbellata Thunb. Ohwi and Ohashi) protection against Callosobruchus maculatus F." by presence of protein profile. (March 2020) - Kaur, Harmeet; Gill, R.S.; Kaur, Satvir
Abstract: To identify defence responses of rice bean against Callosobruchus maculatus, 10 genotypes of rice bean and a mungbean variety, PAU 911 as susceptible check were evaluated. The rice bean genotypes were found to restrain the growth and development of C. maculatus at different larval stages. To justify these results, seeds of different test genotypes were examined for the presence of plant protease inhibitors which inhibit insect proteases causing reduction in the availability of amino acids necessary for their growth and development. Trypsin, chymotrypsin and cysteine protease inhibitor content was significantly higher in rice bean genotypes which ranged from 299.99 to 342.97 TIU g −1 seeds, 235.07 to 251.45 CIU/g seeds and 1060.70 to 1574.99 CPIU/g seeds, respectively as compared to mungbean variety, PAU 911 (235.52 TIU/g seeds, 217.91 CIU/g seeds and 499.99 CPIU/g seeds, respectively). The protein profile showed a polypeptide band of 25–30 kDa corresponding to presence of protease inhibitors in rice bean genotypes except PAU 911. The results indicate that protease inhibitors in different genotypes of rice bean are very effective against C. maculatus. Highlights: Seeds of different rice bean genotypes were examined for the presence of plant protease inhibitors. Protease inhibitors content was higher in all rice bean genotypes than check mungbean variety. Protease inhibitors in rice bean genotypes showed negative impact on C. maculatus development.